Geographic Information System (GIS) Based Android Application for Mapping Geothermal Potential Areas - Ramaditya Firdaus (Journal of Software Engineering, Information and Communication Technology (SEICT), 2022)
Indonesia's dependency on fossil energy to meet domestic energy needs remains relatively high. This dependency is vulnerable to supply shortages as fossil fuels are non-renewable and can be depleted. As a result, fossil energy is depleting, leading to electricity energy crises like the current one. Indonesia's coal reserves are predicted to be depleted within the next 20 years. Optimizing the potential of renewable alternative energy, such as geothermal energy, can fulfill the increasing electricity demand. Indonesia possesses the world's largest geothermal reserves, approximately 40%. Geothermal energy utilization is highly efficient, economical, environmentally friendly, and relatively consistent compared to fossil energy. However, its current utilization is still less than 5%. The limited utilization of geothermal energy is attributed to the management mechanisms of geothermal areas, where construction progress in several locations has been hindered. Therefore, a Geographic Information System (GIS) is needed for mapping the areas with geothermal potential as fuel for geothermal power plants (PLTP). This research generally consists of three phases: (1) data collection, (2) designing a prototype based on an application developed using Android Studio, and (3) conducting application testing using the black box method. The research aims to identify the potential of developed and undeveloped geothermal areas. It is expected to assist and facilitate the government or energy managers in managing geothermal energy resources as fuel for Geothermal Power Plants (PLTP) to meet the electricity needs of the community.